2008
DOI: 10.1111/j.1527-3466.2008.00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effect of Vanadyl Sulfate on Ischemia/Reperfusion‐Induced Injury in Rat Heart In vivo Is Mediated by Activation of Protein Kinase B and Induction of FLICE‐Inhibitory Protein

Abstract: Here we explored the mechanism of cardioprotective action of a tyrosine phosphatase inhibitor vanadyl sulfate on myocardial infarction and cardiac functional recovery in rats subjected to myocardial ischemia/reperfusion (MI/R) in vivo. Male Sprague-Dawley rats underwent 30 min heart ischemia by left coronary artery occlusion followed by 24-h reperfusion. Rats were randomized to receive either vehicle or vanadyl sulfate (1 and 5 mg/kg) intraperitoneally 0 min and 30 min after the start of reperfusion. Posttreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 61 publications
0
27
1
1
Order By: Relevance
“…Like other cardioprotective vanadium compounds (30,42,43), VO(OPT) is a potent Akt activator both in vitro (38) and in vivo (18,19,28,47,48). In vitro studies using 3T3-L1 mouse adipocytes demonstrate that treatment with VO(OPT) increased the tyrosine phosphorylation of proteins including the β-subunit of the insulin receptor and insulin receptor substrate-1 (38,48), suggesting that VO(OPT) can inhibit PTPase.…”
Section: Targeting Akt By Vanadium To Inhibit Cardiomyocyte Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Like other cardioprotective vanadium compounds (30,42,43), VO(OPT) is a potent Akt activator both in vitro (38) and in vivo (18,19,28,47,48). In vitro studies using 3T3-L1 mouse adipocytes demonstrate that treatment with VO(OPT) increased the tyrosine phosphorylation of proteins including the β-subunit of the insulin receptor and insulin receptor substrate-1 (38,48), suggesting that VO(OPT) can inhibit PTPase.…”
Section: Targeting Akt By Vanadium To Inhibit Cardiomyocyte Apoptosismentioning
confidence: 99%
“…Until now, four vanadium compounds, namely, sodium orthovanadate (OV) (42,43); vanadyl sulfate (VS) (20,22,30); bis(maltolato)oxovanadium (IV) [BMOV] (21,44,45); and VO(OPT) (18,19,28), have been found to have cardioprotective effects in different heart injury models (Fig. 1).…”
Section: Akt Activator Vanadium Compounds For Treatment Of Cardiac DImentioning
confidence: 99%
“…3 However, drugs targeting activation of Akt have not been developed in the hypertrophy-induced cardiac remodeling. Thus, we hypothesize that stimulator of phosphatidylinositol 3-kinase/Akt signaling likely inhibits cardiac remodeling via upregulation of eNOS in the cardiomyocytes.We [17][18][19] and others 20 have shown that vanadium compounds are potent Akt activators with cytoprotective action …”
mentioning
confidence: 99%
“…We [17][18][19] and others 20 have shown that vanadium compounds are potent Akt activators with cytoprotective action…”
mentioning
confidence: 99%
See 1 more Smart Citation